2011
DOI: 10.1159/000323964
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial: Impact of Glycerin Suppositories on Time to Full Feeds in Preterm Infants

Abstract: Background: Feed intolerance delays achievement of enteral feeding in preterm infants. Parenteral nutrition is associated with cholestasis and increased risk of sepsis. Glycerin suppositories have been used to promote gastrointestinal motility and feed tolerance. Objectives: To investigate whether daily glycerin suppositories (a) reduce the time to full enteral feeding in infants born at <32 weeks’ gestation, and (b) influence feed tolerance, incidence of sepsis or necrotizing enterocolitis, duration of oxygen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
40
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 51 publications
0
40
1
1
Order By: Relevance
“…In comparison with recent studies investigating similar populations of premature infants [21,22,23,24,25], the incidence of NEC observed in our cohort remained in the lower range. Because this study was retrospective and underpowered to detect clinically relevant differences in the proportion of infants with NEC, we cannot exclude a small increase in the incidence of NEC associated with more rapid EF advancement although the data could also suggest a small decrease in the cumulative incidence of NEC and FIP.…”
Section: Discussioncontrasting
confidence: 77%
“…In comparison with recent studies investigating similar populations of premature infants [21,22,23,24,25], the incidence of NEC observed in our cohort remained in the lower range. Because this study was retrospective and underpowered to detect clinically relevant differences in the proportion of infants with NEC, we cannot exclude a small increase in the incidence of NEC associated with more rapid EF advancement although the data could also suggest a small decrease in the cumulative incidence of NEC and FIP.…”
Section: Discussioncontrasting
confidence: 77%
“…The observational study by Shim et al [5] (n = 83) was excluded from the final analysis. Thus, a total of 6 studies (n = 442) assessing different interventions (glycerine suppository/enema, saline enema, oral osmotic contrast agent) for meconium evacuation were eligible for inclusion in the analysis [24,25,26,27,28,29]. The characteristics of these studies are shown in table 1.…”
Section: Resultsmentioning
confidence: 99%
“…2). Four of the 6 studies had TFF as the primary outcome [24,26,27,29], and those by Haiden et al [25] and Saenz de Pipaón Marcos et al [28] had TFF as the secondary outcome. We used the method of Hozo et al [30] to derive the mean and standard deviation from the median and range reported in the original article.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, a recent trial showed that regular glycerin suppositories did not reduce the time to full enteral feeding in infants born at o32 weeks' gestation. 10 To our knowledge, this is the first randomized controlled trial to investigate the impact of rectal stimulation and enemas on the time to acquire a normal stooling pattern. As the intervention was implemented for both genders, our results suggest that the entire range of ELBW infants do not benefit from using a stimulation program such as we used for the improvement of stooling patterns, and that this approach may be harmful.…”
Section: Discussionmentioning
confidence: 98%